The Pemanfaatan Sumber Daya Desa Dengan Pelatihan Pembuatan Sabun Deterjen Cair Berbasis Industri Rumah Tangga - Hastuti Mulang; Ismail Ismail; Imran Tajuddin (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
Utilization of village resources is an effort to develop the independence and welfare of rural communities by increasing knowledge, attitudes, skills, behavior, abilities, awareness, and utilizing resources through establishing policies, programs, activities and assistance that are in accordance with the essence of the problems and priority needs of the village community . The direction of community empowerment in general stems from two main objectives, namely releasing the shackles of poverty and underdevelopment and strengthening the position of the community in the power structure. Compared to the previous product, namely soap, detergent has the advantage of having better washing powder and not being affected by water hardness. In practice, many laundry services use detergents as washing agents because detergents have effective cleaning properties compared to ordinary soap.